2014
DOI: 10.1186/s12883-014-0197-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting one-year mortality in amyotrophic lateral sclerosis patients - data from a population-based registry

Abstract: BackgroundSurvival in amyotrophic lateral sclerosis varies considerably. About one third of the patients die within 12 months after first diagnosis. The early recognition of fast progression is essential for patients and neurologists to weigh up invasive therapeutic interventions. In a prospective, population-based cohort of ALS patients in Rhineland-Palatinate, Germany, we identified significant prognostic factors at time of diagnosis that allow prediction of early death within first 12 months.MethodsIncident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 19 publications
(34 reference statements)
1
25
1
Order By: Relevance
“…In fact, we did not find an association between prediagnosis BMI and ALS survival; only BMI at diagnosis and BMI change between age 40 years and diagnosis were associated with ALS survival. Other studies support the hypothesis that BMI change immediately before ALS diagnosis is both a common feature of ALS and a prognostic factor, whereas evidence that BMI at ALS diagnosis is a prognostic factor is inconsistent, possibly due to small sample sizes in some studies (12,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 91%
“…In fact, we did not find an association between prediagnosis BMI and ALS survival; only BMI at diagnosis and BMI change between age 40 years and diagnosis were associated with ALS survival. Other studies support the hypothesis that BMI change immediately before ALS diagnosis is both a common feature of ALS and a prognostic factor, whereas evidence that BMI at ALS diagnosis is a prognostic factor is inconsistent, possibly due to small sample sizes in some studies (12,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 91%
“…There is evidence that patients with upper motor neuron features alone12 or lower motor neuron features alone12 22–24 tend to survive longer, and that those with cognitive impairment,25 neck weakness,26 weight loss at diagnosis6 and certain genotypes27 28 have a higher overall mortality. Our study did not include information on these factors.…”
Section: Discussionmentioning
confidence: 99%
“…To date, clinical characteristics such as site of onset, respiratory status, ALS Functional Rating Scale (ALSFRS) scores (Cedarbaum et al, 1999) and C9orf72 phenotype status (i.e. a disease-causing repeat expansion mutation in ALS (DeJesus-Hernandez et al, 2011, Renton et al, 2011)) are shown to have some predictive power for prediction of survival (Chiò et al, 2009, Elamin et al, 2015, Scotton et al, 2012, Wolf et al, 2014, Wolf et al, 2015). Prognosis based on these markers, however, often remains too uncertain to be implemented in clinical practice (Elamin et al, 2015) as motor neuron loss might already occur before clinical weakness can be measured (Simon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%